Process intensification strategies for enhanced holocellulose solubilization: Beneficiation of pineapple peel waste for cleaner butanol production. (20th October 2018) - Khedkar, Manisha A.; Nimbalkar, Pranhita R.; Kamble, Sanjay P.; Gaikwad, Shashank G.; Chavan, Prakash V.; Bankar, Sandip B.
Abstract: Biorefinery sector has become a serious dispute for cleaner and sustainable development in recent years. In the present study, pretreatment of pineapple peel waste was carried out in high pressure reactor using various pretreatment-enhancers. The type and concentration effect of each enhancer on hemicellulose solubilization was systematically investigated. The binary acid (phenol + sulfuric acid) at 180 °C was found to be superior amongst other studied enhancers, giving 81.17% (w/v) hemicellulose solubilization in liquid-fraction under optimized conditions. Solid residue thus obtained was subjected to enzymatic hydrolysis that resulted into 24.50% (w/v) cellulose breakdown. Treated solid residue was further characterized by scanning electron microscopy and fourier transform infrared spectroscopy to elucidate structural changes. The pooled fractions (acid treated and enzymatically hydrolyzed) were fermented using Clostridium acetobutylicum NRRL B 527 which resulted in butanol production of 5.18 g/L with yield of 0.13 g butanol/g sugar consumed. Therefore, pretreatment of pineapple peel waste evaluated in this study can be considered as milestone in utilization of low cost feedstock, for bioenergy production. Graphical abstract: Image 1 Highlights: Synergistic effect of pretreatment enhancer was evaluated to maximize sugar release. Physicochemical pretreatment effectively solubilized 0.65 g/g of holocellulose. Hemicellulose breakdown was confirmed by FTIR and SEM analysis. Biobutanol fermentation was successfully performed using pretreated pineapple peel.